POLITIK HUKUM KEDUDUKAN KOMISI PEMBERANTASAN KORUPSI (KPK) DALAM STRUKTUR KETATANEGARAAN INDONESIA - Hutasoit, Magdalena Br; Artina, Dessy; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Highlighting the performance of the executive, legislative and judicialgovernments, which often deviate from the rules and have violated the constitution,causing losses to the state. These deviant acts are rampant acts of corruption that havenever disappeared from the government from the past until now. In fact, the legitimacy ofprevious institutions tends to be questioned, due to the widespread practices ofcorruption, collusion and nepotism that occur in these institutions. This is thebackground that requires an institution that has a special task to eradicate corruptionwithin the Indonesian government, so a new institution was formed in the reform era inIndonesia, namely the Corruption Eradication Commission (KPK). This is because thecriminal act of corruption is defined as an action carried out by individuals in thelegislative, judicial and private institutions whose aim is to benefit themselves and others.increasing the level of public trust in the KPK, it turns out that the state issued a newregulation to the KPK, namely Law of the Republic of Indonesia Number 19 of 2019concerning the Second Amendment to Law Number 30 of 2002 concerning theCorruption Eradication Commission which has become controversial for the publicbecause of several articles that contained in this Law has weakened the position of theCorruption Eradication Commission in carrying out its duties and authority. This is whatunderlies the need for this research.This research is normative legal research. This is based on library researchwhich takes quotations from reading books, or supporting books that are related to theproblem to be researched. Data sources Primary, secondary and tertiary data sourcesare characteristic of this research. This research also uses qualitative data analysis andproduces descriptive data. From the results of the research and discussions carried out,several conclusions were obtained, namely: First, eradicating corruption is a reformmandate that requires government administration that is free from corruption, collusionand nepotism as mandated in Law Number 28 of 1999 concerning State AdministrationPractices. which is Free and Clean from Corruption, Collusion and Nepotism. To carryout this mandate, the Corruption Eradication Commission (KPK) was formed as a bodythat has the authority to investigate, investigate and prosecute criminal acts ofcorruption, therefore it became inevitable that the Corruption Eradication Commissionwas born amidst the ineffectiveness of the Prosecutor and Police in eradicatingcorruption cases in Indonesia. Second, changes were made to the LawKeywords: Corruption Crimes, State Constitutional Structure, Trias Politica